Strategi Peningkatan Kompetensi Mahasiswa Doktoral melalui Kegiatan Nonreguler di PTKIN Studi Pascasarjana UIN Ar-Raniry dan UIN-SU - Syahrizal Abbas; Syarifah Rahmatillah; Sufriadi Ishak; Azmil Umur (Prodi Hukum Tata Negara Islam (Siyasah Syar'iyyah) STAIN Teungku Dirundeng Meulaboh, 2025)
This study aims to explore in depth non-regular academic activities in doctoral programs within the Islamic Religious College (PTKIN) environment, especially the Postgraduate Program of UIN Ar-Raniry and Postgraduate of UIN North Sumatra. Non-regular academic activities are aimed at improving academic capacity in the form of critical, systematic and logical thinking skills, analytical skills, public communication skills and other social and cultural skills. The main problem in the study is how the role of non-regular academic activities in improving the competence of doctoral program students, as well as the challenges and strategies implemented in order to improve the academic competence of doctoral students in the Postgraduate of UIN Ar-Raniry and UIN North Sumatra. The method used in this study is a qualitative research method. Data collection techniques include document studies and in-depth interviews with respondents, namely the Head of Postgraduate, Head of Study Program, Lecturers and Doctoral Students in the Postgraduate of UIN Ar-Raniry and Postgraduate of UIN North Sumatra. The research found that non-regular academic activities play a significant role in improving the academic competence of doctoral students, both in the Postgraduate Program of UIN Ar-Raniry and the Postgraduate Program of UIN North Sumatra. The obstacle faced is the academic atmosphere that is not yet strong enough, because non-regular academic activities are not a routine agenda and formal part of the curriculum, so there is no funding. This obstacle is felt to be very strong in the Postgraduate Program of UIN North Sumatra, while in Aceh there are not many significant obstacles. The strategy to maintain the continuity of non-regular academic activities is to inform the benefits of activities, especially in the context of research preparation, and make it a prerequisite for formal activities.